Living through a Pandemic: How Students Cope - Hollingsworth, Mary Ann (European Scientific Journal, ESJ, 2021)
The Coronovirus pandemic of 2020 has brought much challenge and disruption to the lives of students in elementary through high schools, their families, and their communities. 74 students in a graduate course in human growth and development conducted action research via interviews with volunteers across childhood and adult lifespan stages to ascertain impact and response the the pandemic experience with a special focus on the role of school in that experience. The majority of volunteers were students, with other participants being educators, parents, and various community members. Volunteers were interviewed on reactions to the pandemic experience, positive and negative life experiences both before the pandemic and during the panding that influenced coping, and reflections on what their local schools were doing to facilitate educational functtio Interview responses aligned with research already published on student experience with the pandemic and also produced new insight for future endeavors by the educational community in promotion of d evelopment of protective factors before similar crises occur and optimal interventions by schools during the experience of crises.